Environmental Based IPS Learning Model Based 0n Concepts School-Based Management (MBS) - Hamid Darmadi (Universitas Tanjungpura, 2018)
The result of the research shows: (1) environmentally oriented IPS learning model can foster the love of regional cultural values as the basis of national cultural development, (2) community participation, and government participation in implementing the environment-based IPS learning model positively impact the improvement of management (3) learning model of environment-based IPS effectively creates a peaceful way of life, peacefully enhancing the intensity of togetherness and mutual respect (4) learning model of environment-based IPS can improve student learning outcomes, (5) there are differences in attitude and outcome expression learning between students residing in conflict areas with students outside the conflict area (6) attitude scale analysis between junior high school and high school students gained from the achievement of junior high and senior high school students towards the values of unity and unity of prestige, respect for diversity and peaceful coexistence . It is recommended that the authority of Dinas Pendidikan as an institution for fostering and developing socio-cultural values in the province can apply an environment-based IPS learning model.